Prevalencia del síndrome de desgaste proteico y su relación con la ingesta dietética en pacientes adultos que están sometidos a hemodiálisis en el Hospital General Norte Ceibos, Guayaquil, octubre 2019 - marzo 2020. - López Bastidas, Evelyn Elizabeth (2020)
Protein wear syndrome is a very frecuent at the patient with chronic kidney disease who perform hemodialysis, causing loss of fat and muscle due to the interaction of various factors that directly and indirectly alter protein and energy metabolism. The focus of the studio is determinate the prevalence of protein wasting syndrome and its relationship with dietary intake in patients with chronic kidney disease who perform hemodialysis at the General Hospital del Norte de Guayaquil Los Ceibos. The results that found when applying diagnostic criteria of protein wear proposed by the International Society of Renal Nutrition and Metabolism (ISRNM) measuring biochemical data were 53%m with DPE base on biochemical indicators of prealbumin albumin cholesterol, evaluating body mass criteria, 52% of patient with DPE were obtained according to muscle perimeter of the arm and trough the criteria of dietaty intake, 63.5% of patience with DPE were obtained. The prevalence of protein wasting syndrome and its relation with the dietary ingest in patience who undergo hemodialysis were identified, obtaining a prevalence of 63.5% of patients who have a poor untaken of protein and calories causing continuous wear of protein-energy reserves.